Legalising Forms of Active Cyber Defense (ACD) - Dominika Dziwisz (Politeja)
The article analyzes the legality and implications of active cyber defense (ACD), including the controversial practice of retaliatory hacking (hack-back), by private entities. The author presents the current legal restrictions in the United States, where companies are essentially barred from taking aggressive defense measures beyond their own networks, despite growing cyber threats. The paper discusses the arguments for and against legalizing ACD, including issues of attack attribution, company readiness, the risk of escalating international conflicts, and potential legal consequences. The article focuses on legislative proposals, such as the Active Cyber Defense Certainty Act, aimed at mitigating these restrictions, while pointing out the associated challenges and dangers.